Kafka's Jewish languages : the hidden openness of tradition - Suchoff, David Bruce (Haney Foundation series., 2012)
""In Kafka's Jewish Languages David Suchoff quite persuasively argues that the Germanic interplay between high and low (Yiddish) languages and the rise of modern Hebrew account for far more of the plays and innovations of Kafka's writing than has previously been acknowledged. Suchoff's diligent, innovative, and supremely intelligent work adds significantly to Kafka scholarship and Judaic studies."--Henry Sussman, Yale University After Franz Kafka died in 1924, his novels and short stories were published in ways that downplayed both their author's roots in Prague and his engagement with Jewish tradition and language, so as to secure their place in the German literary canon. Now, nearly a century after Kafka began to create his fictions, Germany, Israel, and the Czech Republic lay claim to his legacy. Kafka's Jewish Languages brings Kafka's stature as a specifically Jewish writer into focus. David Suchoff explores the Yiddish and modern Hebrew that inspired Kafka's vision of tradition. Citing the Jewish sources crucial to the development of Kafka's style, the book demonstrates the intimate relationship between the author's Jewish modes of expression and the larger literary significance of his works. Suchoff shows how "The Judgment" evokes Yiddish as a language of comic curse and examines how Yiddish, African American, and culturally Zionist voices appear in the unfinished novel, Amerika. In his reading of The Trial, Suchoff highlights the black humor Kafka learned from the Yiddish theater, and he interprets The Castle in light of Kafka's involvement with the renewal of the Hebrew language. Finally, he uncovers the Yiddish and Hebrew meanings behind Kafka's "Josephine the Singer, or the Mouse-Folk" and considers the recent legal case in Tel Aviv over the possession of Kafka's missing manuscripts as a parable of the transnational meanings of his writing. David Suchoff is Professor of English at Colby College."--Project Muse.